2009
DOI: 10.1128/jcm.02320-08
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Mycobacterial Yield and Reduced Time to Detection in Pediatric Samples by Use of a Nutrient Broth Growth Supplement

Abstract: There is an urgent need to improve the methods used for the bacteriological diagnosis of childhood mycobacterial disease. This study compared the mycobacterial yields and the times to detection (in days) of mycobacteria in pediatric clinical specimens by using Mycobacterial Growth Indicator Tubes (MGITs) and solid Löwenstein-Jensen (LJ) slants with and without a nutrient broth supplement. A total of 801 specimens from 493 patients were processed: 82.8% were gastric aspirate specimens, 15.6% were sputum specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 17 publications
3
12
2
1
Order By: Relevance
“…Comparable findings were reported in USA with the rate of 82% for BACTEC MGIT and 76% with LJ method [10]. South African study reported almost similar finding with recovery rate of 83% using BACTEC MGIT for smear positive specimens [11]. …”
Section: Discussionsupporting
confidence: 64%
“…Comparable findings were reported in USA with the rate of 82% for BACTEC MGIT and 76% with LJ method [10]. South African study reported almost similar finding with recovery rate of 83% using BACTEC MGIT for smear positive specimens [11]. …”
Section: Discussionsupporting
confidence: 64%
“…In addition, MGIT culture had higher sensitivity and specificity (88 vs. 76 %). Similar results in pediatric population were shown by a study from South Africa that compared mycobacterial yield and time to detection of M. tuberculosis in 801 various pediatric specimens (sputum, gastric aspirates and fine needle aspiration) using MGIT and solid LJ [37]. The yield obtained with MGIT was significantly higher than that obtained with LJ (11 vs. 1.6 %), and the time to detection of mycobacteria using MGIT reduced from 26.8 d to 12.4 d. This technique is promising to improve the diagnosis of tuberculosis in children, but is costly, requiring adequate instruments and trained operator.…”
Section: Culture Techniquessupporting
confidence: 83%
“…This is likely to reflect very low mycobacterial numbers in sputum samples and the time to positivity needs to be shortened, for example, by using simple growth supplementation in the culture medium [29]. Availability of novel rapid diagnostic assays for routine screening such as urine lipoarabinomannan detection [17,30] or nucleic acid amplification tests [16] may further expedite diagnosis and treatment initiation and thereby avert some of these deaths.…”
Section: Discussionmentioning
confidence: 99%